SMS applications: Short Messaging & Result Checking System (SMRCS) / Lau Sook Wai - Lau , Sook Wai (2003)
With the advanced technologies in the Internet, SMS is growing faster and getting more popular among Internet users. Communication through the Internet is not only faster but also more convenient and time saving. Users no longer conveyed important message through simple chat on the telephone or a face-to-face act, but it can be carried out on a special simulator through the Internet. Short Messaging and Result Checking System (SMRCS) is develops with the objective of convenience, efficient, and cost-effective. This report focuses on building an online simulator, which provide more functions and features. It contains the conceptual design for the project, the research done on various field related to the project and also methodology used to develop the software. The system architecture of SMRCS is divided into web client, web server and database. The client sends message by connecting and pass request to the web server that will interact with the database server. The database server will process the request and result is sent back to the web server and finally to the recipient. SMRCS will be developed using Microsoft Visual Studio .NET Professional with Visual Basic.NET on Microsoft Windows 2000 Professional platform with Internet Information Server (HS) as the web server, utilizing database created by Microsoft SQL Server 2000. At the end, this project will implement the entire requirements into a real system and strength and weakness of the system will be analyzed.